Making meaning, making a home: students watching Generations - O'Shea, Catherine Mary (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2005)
This thesis is a reception analysis using qualitative interviews to investigate black students' watching of a South African soap opera, Generations, taking into account the context of a largely white South African university campus. The findings of this study are that students find pleasure in talking about Generations and hold seemingly contradictory views on whether it is 'realistic' or not. The analysis concludes that watching Generations does serve to affirm these students' black identity, since there is a particular need to do so on a campus where black students witness and experience racial discrimination.
Keywords: Generations (Television program); Students, Black -- South Africa -- Attitudes; Television soap operas -- South Africa; Cross-cultural studies -- South Africa